2016
DOI: 10.1002/er.3500
|View full text |Cite
|
Sign up to set email alerts
|

Study on CuO-CeO2/SiC catalysts in the sulfur-iodine cycle for hydrogen production

Abstract: Summary The structure and activity of ceria–copper oxides supported on nanometer silicon carbide (nano‐SiC) particles for sulfuric acid decomposition were studied. The promoting activities and stabilities of CuO–CeO2 complex oxides loaded on nano‐SiC grains were prominently higher than those of CuO–CeO2 without carriers, especially at <800 °C. The results of X‐ray diffraction (XRD), transmission electron microscopy (TEM), and high resolution transmission electron microscopy (HRTEM) showed that copper‐cerium co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
(91 reference statements)
1
13
0
Order By: Relevance
“…The activity of the 4 catalysts in Figure 2 (10g/gcatalyst-h weight hourly space velocity [18]) was high, particularly at > 700°C, and the SO3 conversion ratio was close to the equilibrium decomposition limitation. At 600°C-700°C, the 4 catalysts exhibited different activities.…”
Section: Catalytic Activitymentioning
confidence: 80%
See 2 more Smart Citations
“…The activity of the 4 catalysts in Figure 2 (10g/gcatalyst-h weight hourly space velocity [18]) was high, particularly at > 700°C, and the SO3 conversion ratio was close to the equilibrium decomposition limitation. At 600°C-700°C, the 4 catalysts exhibited different activities.…”
Section: Catalytic Activitymentioning
confidence: 80%
“…This finding indicated that Si and C reaction did not proceed completely during the preparation of silicon carbide, allowing the oxidation of some SiC or Si to SiO2 while the catalyst was burned in air. The spectrum of the CeCu-SiC catalyst showed a significant SiO2 protrusion near the diffraction angle of 20°; thus, that the calcination temperature of 700°C also led to the apparent oxidation of SiC [18].The SiC crystal peak of the CeCu-SiC catalyst was also weak owing to the overlap of peaks. The XRD spectrum of CeCu-SiC-Al2O3 was mainly CeO2, Al2O3, and SiC diffraction peaks, weak diffraction peaks of CuO and SiO2.…”
Section: Catalytic Activitymentioning
confidence: 97%
See 1 more Smart Citation
“…And excess H 2 O is also necessary for making the Bunsen reaction more thermodynamically favorable . As a result, the practical excess amounts of I 2 and H 2 O with respect to their stoichiometric value usually reach 4 to 6 and 11 to 13 according to Lee et al The produced light H 2 SO 4 phase (most H 2 SO 4 , H 2 O and less HI, I 2 ) and the heavy HIx phase (most HI, I 2 , H 2 O and less H 2 SO 4 ) require liquid phase separation and purification before the catalytic decomposition of H 2 SO 4 and HI . A large amount of energy is required to remove and recycle the excess iodine and water after liquid phase separation.…”
Section: Introductionmentioning
confidence: 99%
“…Before the H 2 SO 4 decomposition, concentration of H 2 SO 4 through flashing is usually applied. And then the enriched H 2 SO 4 is decomposed into SO 2 , O 2 and H 2 O . The purified HIx (HI‐I 2 ‐H 2 O) solution should be concentrated, separated and decomposed .…”
Section: Introductionmentioning
confidence: 99%